The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1248/bpb.30.287
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Antimicrobial Activity of Aminoglycosides by Carnosol from Salvia officinalis

Abstract: We found that a crude extract from Salvia officinalis (sage) reduced the minimum inhibitory concentrations (MICs) of aminoglycosides in vancomycin-resistant enterococci (VRE). We isolated the effective compound from the extract and identified it as carnosol, one of diterpenoids. Carnosol showed a weak antimicrobial activity, and greatly reduced the MICs of various aminoglycosides (potentiated the antimicrobial activity of aminoglycosides) and some other types of antimicrobial agents in VRE. Carnosic acid, a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 31 publications
4
41
0
4
Order By: Relevance
“…16,[35][36][37][38] Horiuchi et al demonstrated a synergistic effect of S. officinalis extract with aminoglycosides in elimination of certain infections. 39,40 On the contrary, some studies did indicate no antibacterial activity against E. coli and P. aeruginosa. 41 In general, according to the available literature, the effect of S. officinalis extract against E. faecalis is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…16,[35][36][37][38] Horiuchi et al demonstrated a synergistic effect of S. officinalis extract with aminoglycosides in elimination of certain infections. 39,40 On the contrary, some studies did indicate no antibacterial activity against E. coli and P. aeruginosa. 41 In general, according to the available literature, the effect of S. officinalis extract against E. faecalis is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…officinalis as a source of natural antioxidants used in health care products has been shown to be nontoxic to rat hepatocytes with diluted concentrations of the extract 43) . In addition, Horiuchi et al 33) isolated the effective compounds from S. officinalis extract and identified them as carnosol and carnosic acid. They also claimed that carnosol and carnosic acid increase the gram-positive bacteria cell membrane permeability, thereby improving the diffusion of antimicrobial agents into the cells.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial efficacy of S. officinalis against E. faecalis has been investigated using the agar diffusion method 33,34) . However, the studies had observed the bacterial activity of the extracts against planktonic forms only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria and Growth E. faecium FN-1, 18) used as a donor of chromosomal DNA, was kindly provided by Dr. Y. Ike (Gunma University). This strain is a clinical isolate.…”
Section: Methodsmentioning
confidence: 99%